2020
DOI: 10.1186/s12887-020-1986-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed initiation of enteral feeds is associated with postnatal growth failure among preterm infants managed at a rural hospital in Uganda

Abstract: Background: Prematurity is the leading cause of mortality in children under 5 years of age globally and is also frequently associated with postnatal growth failure (PGF). Although most preterm births occur in low resource settings, little is known about their postnatal growth outcomes especially in rural areas. We evaluated the incidence and factors associated with PGF among preterm infants managed at a rural hospital in Uganda. Methods: Retrospective cohort study of preterm infants discharged from Kiwoko Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…Early initiation of breast milk feeding signi cantly reduced the duration of regaining birth weight more than three days in the intervention group when compared to the controls. This nding demonstrates the bene t of early enteral feeding in the prevention of postnatal growth failure and is consistent with studies from Uganda [12], Iran [25] and India [11,29]. However, this did not correspond with a shortened hospital stay as shown in previous studies [11,25] and may be explained by other factors such as neonatal sepsis which may impact on the early stabilization of the neonates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Early initiation of breast milk feeding signi cantly reduced the duration of regaining birth weight more than three days in the intervention group when compared to the controls. This nding demonstrates the bene t of early enteral feeding in the prevention of postnatal growth failure and is consistent with studies from Uganda [12], Iran [25] and India [11,29]. However, this did not correspond with a shortened hospital stay as shown in previous studies [11,25] and may be explained by other factors such as neonatal sepsis which may impact on the early stabilization of the neonates.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, previous studies have demonstrated that delayed initiation of enteral feeds leads to signi cant postnatal growth failure and adverse neonatal outcomes, especially in low resource settings where total parenteral nutrition for neonates is not readily available [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Early initiation of breast milk feeding signi cantly reduced the duration of regaining birth weight more than three days in the intervention group when compared to the controls. This nding demonstrates the bene t of early enteral feeding in the prevention of postnatal growth failure and is consistent with studies from Uganda [13], Iran [26] and India [12,30]. However, this did not correspond with a shortened hospital stay as shown in previous studies [12,26] and may be explained by other factors such as neonatal sepsis which may impact on the early stabilization of the neonates.…”
Section: Discussionsupporting
confidence: 90%
“…Delayed trophic feeding: indicates when the neonates start trophic feeding after 24 hours of birth. 22 , 23 …”
Section: Sampling Technique and Proceduresmentioning
confidence: 99%